The economic factor in international relations a brief introduction - Economides, Spyros (Library of international relations (Series) ;, 2001)
Economics no longer forms the backdrop to world events but rather appears to drive foreign policy and represents a more powerful resource than military strength. If globalization is irreversible, then conquering markets is much more important than conquering territory. These are the claims made about economics in world affairs, both by policy analysts and by armchair philosophers. This book examines these claims critically shows how political agendas and speculation have formed many of our current assumptions about the workings of economics in the world today.